EFFECTS OF FIBER LENGTH ON FIRE PERFORMANCE OF INTUMESCENT FIRE RETARDANT COATING - AHMAD ZUHAIRIE BIN YAHYA, AHMAD (Universiti Teknologi Petronas, 2012)
The purpose of this study is to examine the effects of fiber reinforcement on the intumescent fire retarding coating to explore the mechanical and chemical properties in order to increase the fire performance of the intumescent fire retardant coating. The coatings were formulated using Ammonium Polyphosphate (APP) as acid source, Expandable Graphite (EG) as carbon source, Melamine as blowing agent, Boric acid as additives, Epoxy as binder and fiber glass was added in strengthening intumescent coating. Different intumescent formulations were developed and fiber glass composition was varied from 0%, 2%, 4%, 6% and 8% and for fiber length were 3mm and 5mm. The steel substrate coated with fire retardant coating was tested using Bunsen Burner Test for fire performance test. The char expansion was measured in experiment of furnace test at 500°C and 800°C. Thermo Gravimetric Analysis (TGA) and X-Ray Diffraction (XRD) were used for residual weight and char composition analysis respectively.